2022
DOI: 10.1177/10732748221130164
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Barriers to Clinical Trials Accrual in Community Cancer Centres Using a National Clinical Trials Navigator:A Cross-Sectional Analysis

Abstract: Introduction Clinical trials, although academically accepted as the most effective treatment available for cancer patients, poor accrual to clinical trials remains a significant problem. A clinical trials navigator (CTN) program was piloted where patients and/or their healthcare professionals could request a search and provide a list of potential cancer clinical trials in which a patient may be eligible based on their current status and disease. Objectives This study examined the outcomes of a pilot program to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The Clinical Trials Navigator developed by the Canadian Cancer Clinical Trials Network was designed to study mitigating such barriers. This pilot program sought to enable health care professionals to search for existing clinical trials more efficiently and ultimately demonstrated a reduction in referral time from nearly 7 days to 1 day . Implementing navigation platforms demonstrably improves physicians’ ability to discuss existing clinical trials with their patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Clinical Trials Navigator developed by the Canadian Cancer Clinical Trials Network was designed to study mitigating such barriers. This pilot program sought to enable health care professionals to search for existing clinical trials more efficiently and ultimately demonstrated a reduction in referral time from nearly 7 days to 1 day . Implementing navigation platforms demonstrably improves physicians’ ability to discuss existing clinical trials with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…This pilot program sought to enable health care professionals to search for existing clinical trials more efficiently and ultimately demonstrated a reduction in referral time from nearly 7 days to 1 day. 20 Once a clinical trial is identified for an eligible patient, the patient must then decide whether to participate. Common reasons that patients decline participation in a clinical trial include fear of adverse effects, negative attitude due to hearsay or personal experience, cultural appropriateness, lack of communication between physician and patient, and financial and/or logistical difficulties.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…Participation in clinical trials is recommended as part of the clinical care for cancer patients in most guidelines, yet patient accrual is poor [ 1 ]. Lack of awareness, understanding and accessibility of trials are commonly reported barriers [ 2 , 3 ]. Furthermore, participant enrollment is notoriously low in community-based hospitals compared to academic centres [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge in community hospitals is the lack of availability of clinical trials at their home centre. In Ontario, non-academic cancer centres run between 1 and 15 clinical trials at any one time, as compared to 100–350 trials in the larger, academic centres [ 2 ]. This adds a unique challenge to the community-based oncologist who needs to look outside of their cancer centre to increase access for clinical trials for their patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation